SÍNTESE, CARACTERIZAÇÃO E ATIVIDADE FOTOCATALÍTICA DE NANOCATALISADORES DE Fe2O3 PARA DEGRADAÇÃO DE RODAMINA B - Muraro, Pâmela Cristine Ladwig (2019)
The presence of toxic organic and inorganic compounds in wastewater is one of the major environmental pollution problems, significantly compromising the balance of the aquatic ecosystem and public health. In addition, the textile industries are mainly responsible for the generation of significant amounts of colored wastewater containing organic dyes, such as rhodamine B (RhB), with toxic, mutagenic and carcinogenic properties, as well as low biodegradability. Then, the aim of the present work was to study the synthesis, characterization and photocatalytic activity of iron oxide nanocatalysts doped with metallic nanoparticles (TiNPs and AgNPs), in order to the degradation by heterogeneous photocatalysis of RhB dye in aqueous solution. For the Fe2O3 nanocatalyst synthesis , the chemical precipitation method was used by reducing reagent method (sodium borohydride), while the nanocatalysts doped with the nanoparticles impregnation methodology (25% m/m), followed by calcination (450 °C and 4 hours). The nanocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), infrared spectroscopy with Fourier transform (FT-IR), nitrogen porosimetry (BET/BJH method), zeta potential (ZP), diffuse reflectance spectroscopy (DRS) and antimicrobial activity. To evaluate photocatalytic activity, photocatalytic tests were performed in a slurry reactor, with the nanocatalyst in suspension, using as a target molecule the RhB, under ultraviolet (UV) and visible radiation. Initially, it was evaluated the influence of the main operational variables on the degradation and specific reaction velocity, such as catalyst concentration (0.5 -5 g L-1), pH of the reaction medium (2 - 12) and initial concentration of RhB (20 - 100 mg L-1), as well as the influence of photolysis and adsorption on the degradation of the dye. Then, the experimental design was performed with DCCR 2³ effects test and defined the ideal operating conditions ([Fe2O3] = 1.4 g L-1, pH = 10 and [RhB] = 24.2 mg L-1), with a degradation of 77.4% (k = 0.0124 min-1), after 120 minutes of photocatalytic reaction. Therefore, the photocatalytic activity of the nanocatalysts (doped or not) was evaluated in these ideal conditions, where the AgNPs-Fe2O3 sample showed the best photocatalytic activity with a degradation of the RhB dye of 94.1% (k = 0.0222 min-1, under ultraviolet radiation) and 58.4% (k = 0.007 min-1, under visible radiation), while under the same conditions, the TiO2-P25 commercial catalyst showed a degradation of 61.5% (k = 0.0078 min-1) and 44.5% (k = 0.0044 min-1), respectively. According with the ideal conditions determined, another 9 important factor was measured was the AgNPs-Fe2O3 nanocatalyst reuse, showing a short reduction (about 8%) of its photocatalytic activity after 5 cycles. Therefore, doping with TiNPs and AgNPs promoted changes in the structural, texture and catalytic properties of the synthesized samples, such as decrease of the band gap energy (Eg), increase of the surface area (SBET) and improve of the photocatalytic activity. Thus, the Fe2O3 nanocatalyst (doped or not) can be considered a promising catalyst in the heterogeneous reaction of photocatalysis for application in the degradation of organic dyes in aqueous solution.